Pollution du milieu marin. Toxicite du fuel rose et du dichlorure de mercure - BEJI, Othman (INSTM Bulletin : Marine and Freshwater Sciences, 1985)
The bichlorure of mercury has a first apparent phase of inactivity. It operates slowly and its toxicity increases with time of exposure in the toxic solution. The water insoluble fuel was found to be not toxic in 24 and 48 h exposures, even for the maximal dose tested (2 ml/l).